ZUBIZARRETA, Patxi. Barrikadak.: Alberdania argitaletxea, Irun, 2003 94 orrialde - Arozena, Ainhoa (EGAN, 2021)
AINHOA AROZENA: ZUBIZARRETA, Patxi. Barrikadak. Alberdania argitaletxea, Irun, 2003 94 orrialde